2016
DOI: 10.1097/jtn.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of Concussions and Concussion-Like Symptoms in Female High School Athletes

Abstract: Underreporting of concussions and concussion-like symptoms in athletes continues to be a serious medical concern and research focus. Despite mounting worry, little evidence exists examining incidence of underreporting and documenting characteristics of head injury in female athletes participating in high school sports. This study examined the self-reporting behaviors of female high school athletes. Seventy-seven athletes participated, representing 14 high school sports. Nearly half of the athletes (31 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 22 publications
1
43
1
Order By: Relevance
“…Similar studies have provided other definitions for concussion and found varying self-reported incidence rates of concussion. McDonald, Burghart, and Nazir (2016) assessed the concussion reporting behaviors among female high school athletes and found the reported incidence rate to be much higher than our findings, with approximately 40% of athletes reporting a suspected concussion. A cross-sectional survey by Register-Mihalik et al (2013), using a convenience sample of high school athletes from nine different states, found that more than half (53%) of athletes recalled sustaining at least one possible concussion.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Similar studies have provided other definitions for concussion and found varying self-reported incidence rates of concussion. McDonald, Burghart, and Nazir (2016) assessed the concussion reporting behaviors among female high school athletes and found the reported incidence rate to be much higher than our findings, with approximately 40% of athletes reporting a suspected concussion. A cross-sectional survey by Register-Mihalik et al (2013), using a convenience sample of high school athletes from nine different states, found that more than half (53%) of athletes recalled sustaining at least one possible concussion.…”
Section: Discussioncontrasting
confidence: 74%
“…Rivara et al (2014) found that 69% of concussed athletes reported playing with symptoms and 40% said that their coach wasn’t aware of their injury. Similarly, McDonald et al (2016) found that nearly a third of athletes did not report their concussion symptoms to athletic training staff after their injury. This points to the complexity of concussion as a public health issue and the discrepancies between behavioral intentions and actual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…. Muthuswamy, 2013;Covassin & Elbin, 2011;McDonald, Burghart, & Nazir, 2016). Participants in the focus groups were not matched by sport.…”
Section: Methodsmentioning
confidence: 99%
“…4 As in other sports, the total number of concussions and other head injuries in football appears to be underreported. [6][7][8] Head injuries include all injuries caused by a direct or indirect blow against/transmitted to the head and can result in substantially different central and peripheral outcomes, ranging from no detectable functional effects to transient functional impairments, from absent to major structural lesions, and from clinically absent to life-threatening deficits. [9][10][11][12] A differentiation between injuries of the brain, the skull, the face, the cervical spine, or the inner ear (vestibular and cochlear labyrinth) is often not possible on-pitch or off-field, 13 especially since combined injuries of different central and peripheral systems (eg, brain, cervical, vestibular, cochlear, and ophthalmological) are frequent.…”
Section: Introductionmentioning
confidence: 99%